The role of transposable elements in the regulation of IFN-lambda1 gene expression. - Thomson, S; Goh, F; Banks, H; Krausgruber, T; Kotenko, S; Foxwell, B; Udalova, I (2009)
IFNs lambda1, lambda2, and lambda3, or type III IFNs, are recently identified cytokines distantly related to type I IFNs. Despite an early evolutionary divergence, the 2 types of IFNs display similar antiviral activities, and both are produced primarily in dendritic cells. Although virus induction of the type I IFN-beta gene had served as a paradigm of gene regulation, relatively little is known about the regulation of IFN-lambda gene expression. Studies of virus induction of IFN-lambda1 identified an essential role of IFN regulatory factors (IRF) 3 and 7, which bind to a regulatory DNA sequence near the start site of transcription. Here, we report that the proximal promoter region of the IFN-lambda1 regulatory region is not sufficient for maximal gene induction in response to bacterial LPS, and we identify an essential cluster of homotypic NF-kappaB binding sites. Remarkably, these sites, which bind efficiently to NF-kappaB and function independently of the IRF3/7 binding sites, originate as transposable elements of the Alu and LTR families. We also show that depletion of the NF-kappaB RelA protein significantly reduces the level of the IFN-lambda1 gene expression. We conclude that IFN-lambda1 gene expression requires NF-kappaB, and we propose a model for IFN-lambda1 gene regulation, in which IRF and NF-kappaB activate gene expression independently via spatially separated promoter elements. These observations provide insights into the independent evolution of the IFN-lambda1 and IFN-beta promoters and directly implicate transposable elements in the regulation of the IFN-lambda1 gene by NF-kappaB.